Pendampingan Pembelajaran di Masa Pandemik Covid-19 dengan Pendekatan Drive Thru di TK Al-Quran Plus Darussalam Kabupaten ProbolinggoRAN PLUS DARUSSALAM KABUPATEN PROBOLINGGO - Tri Wisudaningsih, Endah; Hifdil Islam, Muhammad (KHIDMAH : Jurnal Pengabdian Masyarakat, 2021)
Abstrak. : Community service Aims To Provide a Learning Aid in the Covid-19 pandemic with the approach of the Drive Thru in KINDERGARTEN Al-Quran plus Darussalam Kabupatenolinggo. Help to ustadzah and guardians of students in KINDERGARTEN Al-Quran plus Darussalam Kraksaan in managing the learning process by using the Drive Thru. This activity is carried out in several stages, namely (1) Identification of Problem (2) Analysis (3) designing mentoring (4) implement guidance (5) monitoring and Evaluation of the Results of (6) and plan to follow up. The result of this devotion in the form of mentoring, learning approach online using the Drive Thru to Ustadzah through the learning activities in KINDERGARTEN Al-Quran plus Darussalam Sub Krakolinggo, this area confirm the green zone by the government so that penulaan dare to do devotion in this place. This activity provides many benefits, new insights and knowledge to Ustadzah and guardians of learners. Keywords: KINDERGARTEN; Mentoring, Learning Pandemic Covid-19